Research on access control for secure cross-domain data circulation - LI Heng; LI Fenghua; SHI Xinyi; GUO Yunchuan; GUO Shoukun (Tongxin xuebao)
To address security risks such as tampering, leakage, and misuse of information stemming from inconsistent authorization mechanisms in data element circulation, the focus was placed on secure cross-domain data circulation. Initially, the challenges associated with cross-domain data access control were systematically examined, followed by an in-depth investigation into the fundamental concepts of cross-domain data circulation and the essential implications of cross-domain access control. Subsequently, a comprehensive review was conducted on access control technologies for secure cross-domain data circulation, which encompassed: access control models categorized as provenance-based, purpose-based, and cyberspace-oriented approaches; key policy management technologies involving label mining for policies, policy negotiation and generation, conflict detection and resolution, policy propagation and enforcement, and auditing of anomalous policy execution; policy implementation mechanisms developed based on blockchain technology, data capsules, and data infrastructure. Finally, current challenges in cross-domain data circulation are systematically summarized, and future research directions are proposed.